ZIF-8 Films and Surface Plasmon Resonance for Chemical Vapor Detection - Anna Estany-Macià; Ignasi Fort-Grandas; Nirav Joshi; Winnie E. Svendsen; Maria Dimaki; Albert Romano-Rodríguez; Mauricio Moreno-Sereno (Proceedings)
In this paper, we present a sensor that employs Zeolitic Imidazolate Frameworks (ZIF-8) on a Surface Plasmon Resonance sensor based on diffraction gratings to detect ethanol vapors via refractive index change in the porous structure.